2018
DOI: 10.1021/acschembio.8b00654
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Activities of the Functional Structures of a Glycolipid Essential for Membrane Protein Integration

Abstract: MPIase is the first known glycolipid that is essential for membrane protein integration in the inner membrane of E. coli. Since the amount of natural MPIase available for analysis is limited and it contains structural heterogeneity, precisely designed synthetic derivatives are promising tools for further elucidation of its membrane protein integration mechanism. Thus, we synthesized the minimal unit of MPIase, a trisaccharyl pyrophospholipid termed mini-MPIase-3, and its derivatives. Integration assays reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 46 publications
4
54
0
1
Order By: Relevance
“…These results suggested that the Sec/SRP-independent integration was generally controlled by DAG and MPIase. Structure-activity relationship studies revealed that the anchoring of MPIase in the membrane by its lipid moiety is essential for the membrane protein integration ( 13 ). The E. coli cell membrane is composed of a wide variety of lipid molecules that dynamically interact with each other.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results suggested that the Sec/SRP-independent integration was generally controlled by DAG and MPIase. Structure-activity relationship studies revealed that the anchoring of MPIase in the membrane by its lipid moiety is essential for the membrane protein integration ( 13 ). The E. coli cell membrane is composed of a wide variety of lipid molecules that dynamically interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The number of repeating trisaccharide units ranges from 7 to 14 but most are 9–11. Polysac-P was obtained by pyrophosphatase digestion of natural MPIase ( 12 , 13 ). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our rst target compound was the minimal unit of MPIase, a trisaccharyl pyrophospholipid termed mini MPIase 3 (1) ( Figure 3). 14…”
Section: Syntheses Of Mpiase Derivativesmentioning
confidence: 99%